2009
DOI: 10.1016/j.neulet.2008.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific loss of κ-opioid receptors in oligodendrocytes of the dysmyelinating jimpy mouse

Abstract: Jimpy is a murine mutation in myelin proteolipid protein, leading to premature death of oligodendrocytes and severe central nervous system hypomyelination. Jimpy is a bona fide model of human Pelizaeus-Merzbacher disease. This paper describes a severe reduction in expression of κ-opioid receptors (KOP) in oligodendrocytes of jimpy mice. A cell specific reduction of >90% is apparent by 5 days of age. Expression is not reduced in neurons, and μ-opioid receptor expression is normal. Mechanism(s) leading to defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 50 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…Nor-BNI greatly enhanced glutamate-induced death of oligodendroglia while causing only modest effects on its own, again invoking the issue of context in opiate effects on survival as well as growth/differentiation ( 165 ). A relationship between KOR and oligodendrocyte function/myelin production was also suggested by our finding that KOR (but not MOR) was severely reduced on oligodendrocytes, but not neurons, in the jimpy mouse, a dysmyelinating mutant ( 205 ). More recent work has also shown that KOR agonists, including U50,488, can promote differentiation/myelination in human oligodendrocytes derived from immortalized pluripotent stem cells ( 206 ).…”
Section: Oligodendrocytessupporting
confidence: 62%
“…Nor-BNI greatly enhanced glutamate-induced death of oligodendroglia while causing only modest effects on its own, again invoking the issue of context in opiate effects on survival as well as growth/differentiation ( 165 ). A relationship between KOR and oligodendrocyte function/myelin production was also suggested by our finding that KOR (but not MOR) was severely reduced on oligodendrocytes, but not neurons, in the jimpy mouse, a dysmyelinating mutant ( 205 ). More recent work has also shown that KOR agonists, including U50,488, can promote differentiation/myelination in human oligodendrocytes derived from immortalized pluripotent stem cells ( 206 ).…”
Section: Oligodendrocytessupporting
confidence: 62%
“…Chronic oxycodone exposure in rats causes some axonopathies and reduces the size of axonal fascicles, decreases myelin basic protein levels, and causes the accumulation of amyloid-β precursor protein (APP) (Fan et al 2018). Most preclinical studies have examined the effects of opioids and opioid receptor blockade on OL maturation and/or the timing of myelination (Hauser et al 1993;Knapp et al 1998;Stiene-Martin et al 2001;Sanchez et al 2008;Knapp et al 2009;Vestal-Laborde et al 2014). OLs can transiently express MORs and other opioid receptor types (Knapp et al 1998;Tryoen-Toth et al 2000;Knapp et al 2001;Stiene-Martin et al 2001).…”
Section: White Matter/oligodendroglial Pathologymentioning
confidence: 99%
“…The 158N and 158JP cell lines were derived from normal and Jimpy mice, respectively, and display features of well-differentiated oligodendrocytes [21]. A mutation in the proteolipid protein PLP/DM20 in Jimpy mice causes premature death of oligodendrocytes and leads to severe CNS demyelination [22]. In comparison to 158N cells, 158JP cells were observed to have significantly higher spontaneous ROS at baseline [21].…”
Section: Cell Culture and Experimental Conditionsmentioning
confidence: 99%